2020
DOI: 10.1186/s13041-020-00575-8
|View full text |Cite
|
Sign up to set email alerts
|

The origin and development of subcortical U-fibers in gyrencephalic ferrets

Abstract: In the white matter of the human cerebrum, the majority of cortico-cortical fibers are of short range, connecting neighboring cortical areas. U-fibers represent connections between neighboring areas and are located in the white matter immediately deep to the cerebral cortex. Using gyrencephalic carnivore ferrets, here we investigated the neurochemical, anatomical and developmental features of U-fibers. We demonstrate that U-fibers were derived from neighboring cortical areas in ferrets. U-fiber regions in ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“… 15 Unique anatomical, developmental and cellular SWM properties may lead to particular vulnerabilities to Alzheimer’s disease-related pathology. For example, short, thin fibres prevalent in SWM are the last WM outside the cortex to myelinate, 16 , 17 which means oligodendrocytes in these regions may be more vulnerable to metabolic insults. 18 , 19 SWM contains the highest density of interstitial cells in WM that harbour neurofibrillary tangles.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Unique anatomical, developmental and cellular SWM properties may lead to particular vulnerabilities to Alzheimer’s disease-related pathology. For example, short, thin fibres prevalent in SWM are the last WM outside the cortex to myelinate, 16 , 17 which means oligodendrocytes in these regions may be more vulnerable to metabolic insults. 18 , 19 SWM contains the highest density of interstitial cells in WM that harbour neurofibrillary tangles.…”
Section: Introductionmentioning
confidence: 99%
“…MRI and histological analyses of U-fibers have been performed on human and monkey brains, but fibers corresponding to the IFL and the OFL have not been reported in mice, making an investigation of U-fibers difficult. Taken together, these results suggest that ferrets are a useful model organism for investigating U-fibers ( Yoshino et al, 2020 ).…”
Section: Evolution and Development Of The Fiber Layer In The Cerebral...mentioning
confidence: 72%
“…Because U-fibers can be visualized in ferrets by expressing GFP using in utero electroporation, we performed similar experiments using mice. Interestingly, a small number of GFP-positive axons that project to neighboring cortical areas were observed in mice ( Saito et al, 2019 ; Yoshino et al, 2020 ). This result suggests that a small number of axon fibers corresponding to U-fibers found in humans, monkeys and ferrets also exist in mice, and these axon fibers have increased significantly during evolution, forming the OFL ( Figure 5A , red) ( Saito et al, 2019 ; Yoshino et al, 2020 ).…”
Section: Evolution and Development Of The Fiber Layer In The Cerebral...mentioning
confidence: 99%
“…Previous studies have demonstrated that short-range fibers have more myelin than long-range fibers. 9,38 Injury to long axons in MS, which eventually causes the fragmentation of fibers, is secondary to myelin loss and may be the consequence of trophic disturbances after mixed outcomes of cumulative interactions among oligodendrocytes, microglia, and neurons. 36 Most interesting, the ODIs of short fibers showed no significant difference between 2 groups because ODI reflects only neurite orientation, which is not sensitive to demyelination.…”
Section: Short-range Connections Are More Severely Damaged In Early-s...mentioning
confidence: 99%
“…However, it could also be that we have failed to identify some tissue injuries within the current T1-/T2-weighted MR imaging, especially those leukocortical lesions located in the connections between anatomic neighboring areas of the cerebral cortex (short-range fibers). 11,38,40 These leukocortical lesions running through the Ufibers in patients have been defined as cortical type I lesions. 41 Cortical demyelination occurs early and is common in patients with MS, and it develops independent from WM lesions.…”
Section: Potential Invisible Leukocortical Lesionsmentioning
confidence: 99%